Motivational predictors of prosocial and antisocial behaviour in football - Kavussanu, M. (Journal of Sports Sciences, 2006)
This study examined (a) the main and interactive effects of goal orientations and perceived motivational climate on prosocial and antisocial behaviour, and (b) whether number of seasons one has played for the team interacts with motivational climate in predicting prosocial and antisocial behaviour in association football. Participants were 325 male association football players, whose age ranged from 12 to 17 years. Athletes completed questionnaires measuring frequency of prosocial and antisocial behaviours in football, goal orientation, motivational climate and social desirability, and indicated the number of seasons they had played for their current team. Regression analyses revealed that task orientation and mastery climate were positive predictors of prosocial behaviour, whereas ego orientation and performance climate were positive predictors of antisocial behaviour. In addition, task orientation negatively predicted antisocial behaviour, while ego orientation negatively predicted prosocial behaviour. No significant interactions between task and ego orientation and mastery and performance motivational climate were found. Finally, mastery climate negatively predicted antisocial behaviour for those who had played many seasons for the team. In conclusion, strengthening task orientation and mastery climate and weakening ego orientation may enhance prosocial behaviour. However, for antisocial conduct to be eliminated from the context of association football, ego orientation and performance climate need to be tempered, as these constructs exert unique independent effects on antisocial behaviour.